PSYCHOLOGICAL FEATURES AND OPERATION OF MYTHS IN THE CONTEXT OF FAMILY PSYCHOLOGY - Harutyunyan, N.A.; Antonyan , S. A. (Modern Psychology, 2020)
The article focuses on one of the key aspects of family psychology and psychotherapy - family myths. The work theoretically analyzes a number of positions, approaches and views known in the professional literature, which in essence reveal the types of family myths, the peculiarities of formation, their functions, the effects of influences on family relations, etc. An attempt was made to study and analyze family myths with social-psychological approaches. The aim of the organized research was to reveal the connection between family myths and the socio-psychological characteristics of the family: adaptation and consolidation. The results show that the socio-psychological features of the family are mostly conditioned not by the degree of general expression of mythology, but by the nature and content of the family myth. The results of the research can be useful in  therapeutic work with families, as well as can be a basis for studying the problems of young families in terms of family myths.
Keywords: Family myths; irrational judgments; «we are the image»; socio- psychological features of the family; family cohesion; adaptation